Women Education in Remote Areas of AJK: Scope of Open & Distance Education - Ahmed, Waqas; Aziz, Maria; Bibi, Irum (PJDOL, 2024)
This research paper explores the problems, challenges and opportunities for women’s education in remote areas of Pakistan and Azad Jammu Kashmir. Quantitative approach of research has been used for this study. A survey form consisting of five open ended questions have been used to collect data from both literate and illiterate women. According to economic survey of Pakistan overall literacy rate of Pakistan is 62.6% in which 73.3% are male and 51.9% are female. Literacy rate of rural areas women are very lower as compared to urban areas women which is only 40.8%. Lack of motivation, cultural norms and conservative attitude towards genders, patriarchal culture, lack of educational facilities, illiterate family environment, family support, resource management, poverty, family and society barrier, early child marriages, non-availability of transport and limited knowledge towards Islam are the main problems and challenges of women education in rural areas. Despite these issues and challenges government and higher education commission of Pakistan are trying their best to resolve these issues and promote women education especially in the rural areas. In this regard, open and distance education is the solution and may be utilized as way forward to promote women education.